Pediatric Pseudotumor Cerebri Syndrome Secondary to Superior Sagittal Sinus Thrombosis Associated with Severe Acute Respiratory Syndrome Coronavirus 2 Infection and Brief Literature Review - Mehmet Can Yeşilmen; Çağatay Günay; Gamze Sarıkaya Uzan; Özlem Özsoy; Semra Hız Kurul; Elif Yaşar; Uluç Yiş (Galenos Publishing House, 2023)
Pseudotumor cerebri syndrome (PTCS) is characterized by the presence of elevated intracranial pressure in the environment of intact brain parenchyma and cerebrospinal fluid (CSF). PTCS can occur in pediatric populations and cause permanent vision loss if left untreated. It is known that evere acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection predisposes patients to adverse arterial and venous thromboembolic events. Several reports from the literature suggest that cerebral venous sinus thrombosis (CVST) may be a direct complication of SARS-CoV-2 infection. Herein, we have aimed to report a case of PTCS secondary to superior sagittal sinus thrombosis associated with the first episode of pediatric SARS-CoV-2 infection. A previously healthy 13-year-old boy presented to the emergency department in February 2022 with complaints of headache, tinnitus and double vision persisting for four days. His mental status and cranial nerve examination results were normal as revealed during neurological examination performed at admission, but bilateral papilledema was detected in fundoscopic examination. SARS-CoV-2 polymerase chain reaction was negative, while anti-SARS-CoV-2 antibody test was positive. There was no variant study in the case. Contrast-enhanced brain magnetic resonance imaging showed signs of intracranial hypertension and magnetic resonance venography demonstrated the presence of superior sagittal sinus thrombosis. CSF opening pressure was elevated (73 cm H2O). As measured during lumbar puncture Our patient was accepted as a case of PTCS secondary to CVST associated with SARS-CoV-2 infection. PTCS secondary to CVST associated with SARS-CoV-2 infection was diagnosed and the child was treated with oral topiramate and low-molecular weight heparin. After the treatment, his headache and visual functions improved and then the child was included in our follow-up protocol. Clinicians should consider the risk of acute CVST in SARS-CoV-2 positive patients, especially if neurological symptoms develop. Prompt diagnosis and treatment can prevent vision loss.